2011
DOI: 10.1097/qad.0b013e328347bd77
|View full text |Cite
|
Sign up to set email alerts
|

Gold drug auranofin restricts the viral reservoir in the monkey AIDS model and induces containment of viral load following ART suspension

Abstract: These findings represent a first step towards a remission of primate lentiviral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 44 publications
6
106
0
1
Order By: Relevance
“…The mechanism of action of auranofin and BSO is likely three-fold (Figures 2 and 3). First, auranofin causes a reduction in the viral reservoir as a direct consequence of the proapoptotic and prodifferentiating effects of auranofin on memory T cells (26,27) harboring the bulk of latent virus (ref. 104 and Figure 2).…”
Section: Treating Hiv/aids By Increasing Oxidative Stress: Results Frmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of action of auranofin and BSO is likely three-fold (Figures 2 and 3). First, auranofin causes a reduction in the viral reservoir as a direct consequence of the proapoptotic and prodifferentiating effects of auranofin on memory T cells (26,27) harboring the bulk of latent virus (ref. 104 and Figure 2).…”
Section: Treating Hiv/aids By Increasing Oxidative Stress: Results Frmentioning
confidence: 99%
“…Trx upregulation is observed in murine splenic B lymphocytes following the initial oxidative burst (24). Conversely, inhibition of the Trx system impairs the mitogenic response of mouse splenocytes (25), favors ASK1-mediated cell death of CD4 + T lymphocytes (26), and downregulates costimulatory CD27 and CD28 molecules in T cells (26,27). The GSH system is also necessary for efficient lymphocyte proliferation.…”
Section: The Trx and Gsh Systems In Cancermentioning
confidence: 99%
“…Currently, there is a great need for an animal model of HAART in which virus eradication strategies can be explored. Achieving suppression of SIV replication to an extent comparable to that seen in HIV-1-infected humans on HAART is the critical first step in the development of models for viral eradication strategies (12,26). However, it is still not clear what regimen is optimal for suppressing SIV replication in vivo.…”
mentioning
confidence: 99%
“…Controlled studies in monkeys infected with simian immunodeficiency virus (SIV) or simian-human immunodeficiency virus (SHIV) and anecdotal reports on human immunodeficiency virus type 1 (HIV-1)-infected humans, such as the "Boston patients" and the "Mississippi baby," have shown that reduction of the viral reservoir, or inhibition of its formation, is a crucial factor for controlling viral load in the absence of antiretroviral therapy (ART) but is not its only determinant (3)(4)(5)(6). These reports suggest that without complete eradication of the viral reservoir, viral load control in the absence of therapy is transient or incomplete.…”
mentioning
confidence: 99%